2019
DOI: 10.1002/smll.201903296
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive PEG‐Shedding and Targeting Peptide‐Modified Nanoparticles for Dual‐Delivery of Irinotecan and microRNA to Enhance Tumor‐Specific Therapy

Abstract: Irinotecan is one of the main chemotherapeutic agents for colorectal cancer (CRC). MicroRNA‐200 (miR‐200) has been reported to inhibit metastasis in cancer cells. Herein, pH‐sensitive and peptide‐modified liposomes and solid lipid nanoparticles (SLN) are designed for encapsulation of irinotecan and miR‐200, respectively. These peptides include one cell‐penetrating peptide, one ligand targeted to tumor neovasculature undergoing angiogenesis, and one mitochondria‐targeting peptide. The peptide‐modified nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 40 publications
2
56
0
1
Order By: Relevance
“…Conversely, the use of active targeting moieties and cell-penetrating peptides substantially enhances the NP uptake, but at the same time increases the formation of PC, facilitating their opsonization and, thus, reducing greatly their plasma half-life. This formulative dilemma has been undertaken by several groups, and many elegant solutions spawned by the combinations of stealthinducing and uptake-enhancing materials on the same NPs (Juang et al, 2019). These innovative formulations can switch their behavior depending on external stimuli: they can either respond to their chemical and biological milieu, or they can be "activated" by external stimuli.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Conversely, the use of active targeting moieties and cell-penetrating peptides substantially enhances the NP uptake, but at the same time increases the formation of PC, facilitating their opsonization and, thus, reducing greatly their plasma half-life. This formulative dilemma has been undertaken by several groups, and many elegant solutions spawned by the combinations of stealthinducing and uptake-enhancing materials on the same NPs (Juang et al, 2019). These innovative formulations can switch their behavior depending on external stimuli: they can either respond to their chemical and biological milieu, or they can be "activated" by external stimuli.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Therefore, many approaches for the covalent linkage of CPPs to NPs make use of the less frequent functionalities, such as thiols, that are present in cysteine. Free thiols can interact with maleimide residues to form a stable carbon-sulfur bond, as demonstrated by various groups for the covalent attachment of CPPs, such as RF, LMWP, or Tat to liposomes, dendrimers, or protein-based NPs [60][61][62]. Alternatively, the high affinity of noble metals to sulfur, which derives from the soft acid-soft base interaction, can be employed for the direct linkage of sulfhydryl-containing CPPs to the surface of metal NPs, as recently demonstrated for R8 and Tat conjugation to silver, gold, and palladium NPs [63][64][65][66][67].…”
Section: Covalent Attachmentmentioning
confidence: 99%
“…Numerous studies have revealed the capacity of miRNAs to serve as promising therapeutic targets, and to be significant diagnostic or prognostic biomarkers in the treatment of malignant tumors (15)(16)(17). In addition, miRNA-608 has been widely reported to be a tumor suppressor gene and is downregulated Figure 3.…”
Section: Discussionmentioning
confidence: 99%